Filantropi Kemanusiaan Sebagai Praktik Seni untuk Survivalitas Para Pekerja Seni - Suwarno Wisetrotomo; Pradani Ratna Pramastuti (Mudra Jurnal Seni Budaya, 2022)
The outbreak of a novel corona virus or the COVID-19 pandemic has caused a global crisis that affects all aspects of life. The health, economy, social, political and cultural crisis trigger the domino effect that lead to a humanitarian crisis. Since the virus was identified in Wuhan, Hubei Province, China at the end of 2019, it continues to radically affect the world. Globalization, that used to be about speed, progress, celebration, intimacy, and a sense of community, has now turned into slowness, decline, as well as physical and social distance. Indonesian government immediately took action by issuing a series of regulations, such as lockdown, self-isolation, and “new normal” habit when working and socializing; two of which are washing hands and wearing masks. Numerous communities experience stagnation in social, economic, political, cultural and artistic life, as well as the possibility of a food crisis due to the decline of their purchasing power. This situation prompts an initiative and contribution from the community members, including artists, to lend a hand. Art workers contribute in making the basic ends of the communities in need meet by providing masks and food for low-income families as well as Personal Protective Equipment (PPE) for medical personnel, such as nurses and doctors. Furthermore, several projects were also initiated by artists, namely “Dapur Aksi Berbagi”, “Dapur Aksi Tetandur”, “Rengeng-rengeng Sirep Pageblug Maskumambang” by LAURA “Climen Puppet Show: The Collaboration of a Puppeteer and a Painter”, “Wrapped-Rice Art”, Didi Kempot Online Concert, and “Panen Apa Hari Ini”. These projects can be considered as humanitarian philanthropy, which from the perspective of contemporary art, is categorized as an art practice. This research uses the descriptive method. The researchers observe and record various philanthropic acts of these artists carefully in order to describe the events that take place. The researchers then answer why the projects can be categorized as art practices. This research will disclose the potential for a new discourse on the relationship between humanitarian philanthropy conducted by artists and art practices.